The Responsibility of The Substitute Notary For His Error in Making A Notary Deed - Tubagus Fakhri Kurnia (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2022)
Based on Law No. 2 of 2014 amandement of Law No. 30 of 2004 on Notary Position (UUJN) one of the rights that notaries have is the right to leave. Notaries who are temporarily unable to serve or take time off, are required to appoint and appoint replacement notaries. The substitute notary has the same authority and responsibility as the notary but does not rule out making mistakes in making a notary deed. Approach methods are the statutory approach and the conceptual approach. The result of this study is that a substitute notary is fully responsible at any time for any notary deeds it makes (Article 65 UUJN). Writing errors made by substitute notaries so that the sound of copies of deeds and minuta deeds are different, namely can be given civil sanctions in the form of correction of deeds or renvoi and administrative sanctions in the form of verbal reprimands, written reprimands, temporary dismissals, respectful dismissals and dismissals with disrespect.Keywords: Substitute Notary; Acts Against the Law